The influence of musical training on acculturation processes in migrant children. (January 2016) - Frankenberg, Emily; Fries, Kirsten; Friedrich, E Kamala; Roden, Ingo; Kreutz, Gunter; Bongard, Stephan
Music is a promising candidate for the enhancement of cultural integration through increased group cohesion and social support. This study assessed the impact of a music program on elementary school-aged migrants' cultural orientation, as measured via the Frankfurt Acculturation Scale for Children (Frankenberg et al., 2013). The music program is an extension of schools' regular curriculum and provides students with basic introduction to music and instrument lessons (Years 1 and 2), followed by school-wide music performances within an ensemble (Years 3 and 4). Results showed that music program participants who had performed in musical ensembles showed larger increases in orientation to mainstream culture over a period of 1.5 years than control students who had not received extended music tuition. For younger program participants who had not yet participated in ensemble play, no such differences were found. Results indicate that it was the experience of collaborating and performing within a larger group which led to stronger host culture orientation. Thus, programs providing young migrants with the opportunity to perform music within a larger, culturally heterogeneous group can be viewed as an effective intervention to encourage adaptation to mainstream culture and integration within and beyond the classroom.